Resistance, Performativity, and Fragmentation: The Relational Arena of EDI/D in Canadian Higher Education - Marom, Lilach (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2023)
Equity, diversity, inclusion, and decolonizing (EDI/D) have gained discursive centrality in Canadian higher education (HE) yet are criticized as performative. Donald’s work on “ethical relationality” understands colonialism as a denial of relations. Drawing on this work I analyze EDI/D in HE through a lens of relationship building. The study maps three institutional layers of EDI/D. The external layer is centred on confronting overt critique, with discourses about EDI/D as threatening academic freedom becoming more prevalent. The second layer focuses on the “mainstream” adoption of EDI/D. EDI/D became central in terminology, but HE culture is more resistant to change. The inner layer includes those engaged with EDI/D. It is grounded in collaboration, but also in containment and fragmentation of EDI/D initiatives. These layers reveal institutional gaslighting tactics that derail meaningful engagement with EDI/D. For EDI/D to be transformative, HE institutions must ground EDI/D in the difficult process of relationship building.